Sugar beet cells’ cellular and extracellular events taking place in response to drought and salinity - Pavoković, Dubravko; Horvatić, Anita; Tomljanović, Ingrid; Balen, Biljana; Krsnik-Rasol, Marijana (Acta Botanica Croatica, 2023)
Salt and drought stress are important abiotic factors that negatively affect plant growth and yield. To understand how these stress factors affect metabolism at the cellular level, we analyzed cation concentrations and expression of cellular and extracellular proteins, as well as their functions and types. Cells of the industrially important halophyte sugar beet were exposed to 300 mM NaCl and 600 mM mannitol as stressors in modified Gamborg B5 liquid nutrient medium (PG0). Severe stress altered the intracellular concentrations of most of the measured cations. The cellular proteome revealed that both stressors provoked significant differential regulation of 110 cellular proteins. About 80% of the identified proteins were classified in metabolism, energy, or cell rescue, defense and virulence categories. We identified several novel proteins that respond to stress, including a member of the bZIP family of transcription factors, a member of the glycine-rich RNA-binding proteins, and the K+ channel beta subunit. Among extracellular proteins we found previously unreported stress-responsive proteins, a beta-xylosidase and an isoform of chitinase. The obtained results indicate that salt and drought stress disturbed the concentrations of cellular cations and affected the expression of cellular and extracellular proteins in sugar beet cells.